2019
DOI: 10.1155/2019/3707416
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Analysis of Vehicle Shimmy with Consideration of the Coupling Effects of Vehicle Body

Abstract: Based on the Lagrange equation, a 9-degrees-of-freedom shimmy model with consideration of the coupling effects between the motions of vehicle body and the shimmy of front wheels and a 5-degrees-of-freedom shimmy model ignoring these coupling effects for a vehicle with double-wishbone independent front suspensions are presented here to study the problem of vehicle shimmy. According to the eigenvalue loci of system's Jacobian matrix plotted on the complex plane, the Hopf bifurcation characteristics of nonlinear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
(28 reference statements)
0
3
0
Order By: Relevance
“…where F z is the vertical load acting on the wheels, φ is the camber angle of the wheels, and the parameters p C1 , p D1 , p D2 , p BCD1 , p BCD2 , p BCD3 , p E1 , and p E2 are all constants determined for each tire. In this study, the value of φ is 0, and the values of p C1 , p D1 , p D2 , p BCD1 , p BCD2 , p BCD3 , p E1 , and p E2 are listed in Table 2 [37][38][39].…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…where F z is the vertical load acting on the wheels, φ is the camber angle of the wheels, and the parameters p C1 , p D1 , p D2 , p BCD1 , p BCD2 , p BCD3 , p E1 , and p E2 are all constants determined for each tire. In this study, the value of φ is 0, and the values of p C1 , p D1 , p D2 , p BCD1 , p BCD2 , p BCD3 , p E1 , and p E2 are listed in Table 2 [37][38][39].…”
Section: Mathematical Modelingmentioning
confidence: 99%
“…To further analyze the influence of the sprung mass on vehicle shimmy, some scholars have also established different shimmy models with more DOF. The influence of the parameters, such as the road adhesion coefficient, wheelbase, and vehicle mass, on the dynamic stability of the nonlinear system was discussed (Li et al, 2019; Wei et al, 2017). These achievements provide good theoretical supports for further study on vehicle shimmy.…”
Section: Introductionmentioning
confidence: 99%
“…The simulation results show that Hopf bifurcation will occur under the condition of a certain vehicle forward speed. X.G Li [15] built a 9-DOF model considering the coupled motion of the vehicle body on the basis of the 5-DOF system, and compared the two models, and found that the 9-DOF shimmy was more likely to occur in the low-speed zone. D.G Wei [16]established a mathematical model for dual-axle steering mechanism of a multi-axle vehicle considering dry friction to study the mechanism of self-excited shimmy of multi-axle vehicle with dual-axle steering mechanism.…”
Section: Introductionmentioning
confidence: 99%